Saṃskr̥tasāhityaprasūnam = Blossoms of Sanskrit literature - Śarmā, Satyaprakāśa; Chaudhary, Ark Nath; Sharma, Neeraj; Pāṇḍey, Ramākānt (New Bharatiya Book Corporation, 2019)
Festschrift in honor of Satyaprakāśa Śarmā, Sanskritist from Aligarh Muslim University ; comprises contributed research papers.